Forecasting Analysis for Production Planning - Bobi Krisman Berkat Gulo; Serniati Zebua; Aferiaman Telaumbanua (Yayasan Riset dan Pengembangan Intelektual, 2024)
The furniture industry plays a pivotal role in the economy by contributing to employment and meeting household needs. Effective production planning and forecasting are crucial for furniture manufacturers to navigate market uncertainties and optimize resource utilization. This study focuses on